Dall’archeologia preventiva al consciuous planning: La tutela come occasione di ricerca e valorizzazione dei paesaggi storici in Etruria e Sicilia - Brancato, Rodolfo; Carosi, Simona (GEOmedia, 2024)
Protection as an Opportunity for Research and Enhancement of Historical Landscapes in Etruria and Sicily. Over the last few decades, Italy has been a key player, both as a subject and object, in the international debate on the topic of preventive archaeology. After some pioneering experiences dedicated to the evaluation and planning of a preventive approach, significant steps have been taken to stimulate the interest of stakeholders as well in the strategic value of the archaeological data that emerge from surveys and excavations. Despite recent developments in non-invasive investigative techniques, excavation intervention remains very often indispensable: the enhancement of the results implies not only potential advancements in the knowledge of the archaeological landscape but could also constitute the central element of conscious planning.